Synthesis and photophysical properties of conjugated (dodecyl)benzoateethynylene macromolecules: staining of Bacillus subtilis and Escherichia coli rhizobacteria. (28th January 2019) - Concepción García, Ma.; Turlakov, Gleb; Moggio, Ivana; Arias, Eduardo; Valenzuela, J. Humberto; Hernández, Mónica; Rodríguez, Geraldina; Ziolo, Ronald F.
Abstract : The staining of agrobacteria was successfully demonstrated through a benzoateethynylene by fluorescence spectroscopy, laser confocal microscopy and microRaman. Abstract : A series of hydrogen, iodine and triazene terminated (dodecyl)benzoateethynylene oligomers and the homologue polymer were synthesized by a divergent–convergent step-by-step approach and characterized by NMR ( 1 H, 13 C, HSQC) and MALDI-TOF mass spectrometry. The photophysical properties in CH2 Cl2 were analyzed by UV-vis and static and dynamic fluorescence revealing that all of the materials are semiconducting with good fluorescence quantum yields ϕ and lifetimes in the range of ns. The type of terminal group in the oligomers, H, I or triazene, has an important effect on both absorption and emission properties, with the maximum red shifts for I and triazene and with a larger bathochromic effect for the triazene oligomers. The structural distortion of the conjugated backbone increases with the benzoateethynylene moieties (BzE) in the hydrogen terminated oligomers (trimer, pentamer and heptamer) as found by theoretical simulations, which explains why the saturation of the effective conjugation is found for the heptamer (8 nm with respect to the polymer). The hydrogen terminated pentamer showed the highest quantum yield of the series with ϕ = 77%, is soluble in N -methylpyrrolidone and displays a strong CC vibration Raman signal. Its application in staining the Gram-positive Bacillus subtilis and Gram-negative Escherichia coli was investigated under in vitro conditions and was successfully demonstrated by fluorescence and microRaman spectroscopy and laser scanning confocal microscopy.